Role of Engineering Technologist to Solve the Impact of COVID-19 to the Society - Nagarajoo, Karthigesu; Chong, Wai Wai; Chooi, Shir Ley; Akasha, Azeera Hanim (Progress in Engineering Application and Technology, 2020)
The aim of this work is to study the impact of COVID 19 to society and the role of technologists to resolve the issue. Coronavirus disease (COVID-19) is an irresistible infection induced by a newly discovered coronavirus. The virus disseminated immediately from a person when a COVID-19 case coughs or exhales producing droplet that reaches the nose, mouth or eyes of another person. Most people infected with the COVID-19 virus will endure light to moderate respiratory illness and recover without demanding specific treatment. The outbreak of coronavirus is a front and leading a human buskin affecting hundreds of thousands of people. This disease also becomes a severe growing impact on society, the global economy, and education. This paper will discuss the impact of COVID 19 on society. This paper also dedicated to presenting the role of technologist and engineer with a perspective on the evolving situation and implications for the world. The outbreak is going fast, and some of the perspectives in this paper may fall rapidly out of date. However, the data analysis of COVID 19 in the world is going to be rendered in this paper and the information about COVID 19 will be updated in this paper.